Effects of hot air drying temperature and tempering time on the properties of maize starch - Ren, Guangyue; Zhang, Ledao; Zeng, Fanlian; Li, Yebei; Li, Linlin; Duan, Xu (International Journal of Agricultural and Biological Engineering, 2020)
Yellow maize as raw materials, hot air drying was used to reduce moisture content, and the tempering was implemented after drying. This study aimed to investigate the effects of hot air drying temperature and tempering time on the properties of maize starch. The wet milling was used to extract maize starch. Starch yield, protein content, amylose and amylopectin content, transparency and coagulation, solubility index and swelling power, color, pasting properties, and gelatinization properties were researched. The results showed that when the hot air temperature increased, the properties such as starch yield, amylopectin content, transparency, solubility, swelling power, whiteness decreased, and properties such as protein content and amylose content, coagulation, gelatinization temperature increased. Compared to drying temperature, tempering time has a less remarkable effect on the maize starch properties. The maize starch with better whiteness, solubility, swelling power could be obtained by adjusting tempering time.Keywords: maize starch, hot air drying temperature, tempering timeDOI: 10.25165/j.ijabe.20201306.3362Citation: Ren G Y, Zhang L D, Zeng F L, Li Y B, Li Linlin, Duan X. Effects of hot air drying temperature and tempering time on the properties of maize starch. Int J Agric & Biol Eng, 2020; 13(6): 236–241.